Rhizoctonia solani soil infestation in Sweden - Bång, Ulla (MTT, 2007)
Attack of potatoes by Rhizoctonia solani has been a serious problem in Sweden for a long time. Earlier work with this disease in the country was focussed on chemical and alternative treatments of seed tubers. The aim of the work presented here is to investigate the occurrence of soil infestation and incidence of various anastomosis groups under various crop rotations and soil types in various regions of Sweden. The study started in 2003 and is still ongoing. It is financially supported by the Swedish Farmers Association for Agricultural Research, SLF. With the help of local advisers, soil samples are collected from fields with a history of R. solani attacks. Samples are taken from three spots of 25 m2 in each field and the positions of the spots are registered on maps or by GPS, thus making repeated sampling from the same spot possible. The rotations, soil type, pH etc. is well documented for each field. The soil infestation has so far been analysed by means of minitubers as a catch crop. After thorough mixing of the soil it has been distributed in pots wherein the tubers have been planted. After around two months in the dark at +10°C and watered as needed, the occurrence of stem canker and sometimes black scurf on the seed tuber has been registered. The cause of injury has been validated by observations under magnification where the mycelium of R. solani is visible and by putting small pieces of canker tissue on artificial media. R. solani infestation has been found in Swedish soils at levels high enough to cause damage on potato plants grown under conditions extremely favourable for attack of the pathogen. The pathogen was detected most frequently in soil samples collected from fields where potatoes were grown the previous year. The proportion of positive samples progressively declined with increasing numbers of years without potatoes. No evident pattern regarding influence of specific crops in the rotations on the decline of infestation has been found. However, in the northern part of the country, there were very few positive samples compared with the southern part at a similar time span to potato crops. Possible reasons for this will be discussed. In 2006, a collaboration with SCRI in Scotland (Alison Lees) has started aiming at comparing three different methods for detection of R. solani soil infestation: minitubers or Quinoa seeds as catch crops, where the DNA from the latter will be analysed at SCRI, or direct analysis of DNA from soil (quantitative PCR at SCRI). Another goal, achieved simultaneously, is to confirm the occurrence of R. solani AG-3 in Sweden. It is also of interest to investigate the prevalence of other anastomosis groups. This will be done when easily handled methods are available.
Keywords: Ka; Rhizoctonia solani; potato; soil infestation; Sweden